2009
DOI: 10.1183/09031936.00190008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of influenza vaccination on mortality risk among the elderly

Abstract: Estimates of influenza vaccine effectiveness have mostly been derived from nonrandomised studies and therefore are potentially confounded. The aim of the current study was to estimate influenza vaccine effectiveness in preventing mortality among the elderly, taking both measured and unmeasured confounding into account.Information on patients aged o65 yrs from the computerised Utrecht General Practitioner database on eight influenza epidemic periods and summer periods was pooled to estimate influenza vaccine ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…13,23,24 Some authors have suggested using the preinfluenza season as a control period. Many previous studies assessing influenza vaccine effectiveness in older adults described reduced mortality associated with vaccination during the entire year.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13,23,24 Some authors have suggested using the preinfluenza season as a control period. Many previous studies assessing influenza vaccine effectiveness in older adults described reduced mortality associated with vaccination during the entire year.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Therefore, patients who have and who have not received vaccine should have similar risks of outcomes during the summer period after adjustment for measured confounders, with an expected IRR of 1.0 for the summer period. We used effect estimates for the summer period to adjust for residual confounding that occurred during the influenza period using the following formula: 23,24 IRR adjusted = exp(β influenza season -β summer period ) where β is the regression coefficient obtained from Poisson regression models. To calculate 95% CIs for the effect estimates, we resampled 500 times from the distribution of the observed estimates for the influenza and summer periods.…”
Section: Adjustment For Residual Confoundingmentioning
confidence: 99%
See 1 more Smart Citation
“…14 We selected 20 000 participants aged 65-90 years. An important confounder (among others) of the association between influenza vaccination and death was use of health care, which is related to an increased risk of death as well as an increased probability of receiving a vaccination.…”
Section: Clinical Examplesmentioning
confidence: 99%
“…After including a number of confounders in the adjustment model, the exposure-outcome association indeed often appears to stabilize (little change in the estimate of the exposure-outcome association is observed when additional confounders are added). 22,23 This implies that all (important) confounders are included in the model, if confounders are highly correlated. This relative stabilization of the exposure-outcome association upon adjustment for an increasing number of confounders clearly depends on the joint association between confounders.…”
Section: << Figure 3 >>mentioning
confidence: 99%